1982
DOI: 10.1001/jama.247.19.2687
|View full text |Cite
|
Sign up to set email alerts
|

Syncope of unknown origin. The need for a more cost-effective approach to its diagnosis evaluation

Abstract: The records of 121 patients hospitalized in Presbyterian-University Hospital, Pittsburgh, during 1976 to 1980 for syncope of unknown origin were reviewed. The were 58 men and 63 women, whose mean age was 63.1 years. Cardiac monitoring in 67 patients showed abnormalities in seven patients, considered diagnostic of the cause of syncope. In 13 patients with electrophysiologic studies, four patients had abnormal results, suggesting a probable cause for the syncope. Cardiac catheterization in 14 patients showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
4

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(67 citation statements)
references
References 16 publications
2
61
0
4
Order By: Relevance
“…A study in 1982 showed that patients often underwent multiple diagnostic tests despite which a cause of syncope was established in only 13 of 121 patients [44] . With the advent of newer diagnostic tests (e.g.…”
Section: Economic Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study in 1982 showed that patients often underwent multiple diagnostic tests despite which a cause of syncope was established in only 13 of 121 patients [44] . With the advent of newer diagnostic tests (e.g.…”
Section: Economic Implicationsmentioning
confidence: 99%
“…The possible contribution of the EEG is to disclose epileptiform abnormalities; there are no specific EEG findings for any loss of consciousness other than epilepsy. Accordingly, several studies [27,44,[260][261][262][263] conclusively showed that electroencephalographic monitoring was of little use in unselected patients with syncope (level B). Thus, electroencephalography is not recommended for patients in whom syncope is a priori the most likely cause for a transient loss of consciousness; it is beneficial in patients with a relatively high likelihood of epilepsy, such as a history of seizures.…”
Section: Electroencephalographymentioning
confidence: 99%
See 1 more Smart Citation
“…ese studies have found that youth, low weight, rst-time donor status, and past vaso-vagal reaction increase the probability of having a vaso-vagal reaction, but they are not predictive. 13,14 is study was aimed to explore the incidence of adverse reactions after blood donation including the incidence vaso-vagal reaction among the whole blood donors.…”
Section: Incidence Of Immediate Adverse Reaction Of Blood Donationmentioning
confidence: 99%
“…2,8,9 Unfortunately, the approach often undertaken includes low-yield testing (EEG, CT scan, carotid Dopplers, Holter monitor, and cardiac enzymes), 2,4,10 yet even "proper" testing (electrophysiology testing and tilt table testing) can be fruitless. In nearly half of all patients, no diagnosis is secured.…”
Section: See P 46mentioning
confidence: 99%